Network pharmacology and experimental evidence reveal the protective mechanism of Yi-Qi Cong-Ming decoction on age-related hearing loss. (31st December 2022) - Yang, Yi-Fang; Yan, Xi-Rui; Wu, Rui-Xin; Li, Ning; Chu, Min; Dong, Yang; Fu, Shu-Ping; Shi, Jian-Rong; Liu, Qing
Abstract: Context: Yi-Qi Cong-Ming (YQCM) decoction has been widely used to prevent age-related hearing loss (ARHL), the most prevalent neurodegenerative disease in the elderly. Objective: To explore the mechanism of YQCM decoction in the treatment of ARHL. Materials and methods: The chemical constituents of YQCM were screened from the Traditional Chinese Medicine Systems Pharmacology Database. Potential targets of YQCM against ARHL were predicted by DrugBank, GeneCards, and OMIM database. Protein-protein network and enrichment analysis were used for exploring possible molecular mechanisms. Molecular docking and an in vitro model of ARHL by exposing auditory cells with 100 μM H2 O2 for 3 h were applied. Cell viability and mitochondrial membrane potential (ΔΨM) were detected by CCK-8 and high-content analysis. γH2AX and cleaved caspase-3 were detected by Western blot. Results: The main compounds have good affinities with hub targets, especially AKT1, PTGS2, and CASP3. GO and KEGG analysis showed that the main biological process and key targets were related to negative regulation of the apoptotic process. H2 O2 treatment could reduce the cell viability by 68% and impaired ΔΨM, while 90 μg/mL YQCM pre-treatment could restore the cell viability by 97.45% and increase ΔΨM (2-fold higher). YQCM pre-treatment also reduced γH2AX and cleaved caspase-3 protein levels. Conclusions: Our study suggested that YQCM prevents ARHL by modulating the apoptosis process in auditory hair cells. Moreover, this study proved that bioinformatics analysis combined with molecular docking and cell model is a promising method to explore other possible pharmacological interventions of ARHL.